The Continuation of World Short Story Traditions in the Works of H. James (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Henry James was a pioneering figure in 20th-century literature, particularly in the genre of the short story, where his contributions shaped the evolution of narrative techniques. This article explores James' distinctive style, which emphasized psychological realism and the exploration of the human psyche, a departure from the traditional focus on external events. By delving into themes such as self-identity, experience, human relationships, and social change, James' works offer profound insights into the internal conflicts and complexities of human existence. His use of techniques like internal monologue and psychological realism influenced subsequent literary movements and inspired writers like Marcel Proust and Franz Kafka. This article highlights James' lasting impact on modern literature, showing how his innovative approach paved the way for a deeper exploration of human experience in the 20th and 21st centuries.